Stereoselective aza-Michael addition of anilines to 1-nitro cyclohexene by intramolecular protonation. Issue 46 (18th November 2015) - Ghisu, Lorenza; Melis, Nicola; Secci, Francesco; Frongia, Angelo
Graphical abstract: Abstract: An asymmetric synthesis of α-aryl amino-β-nitro cyclohexanes has been achieved by means of a tandem aza-Michael addition-protonation reaction starting from 1-nitro cyclohexene and anilines. The transformation is proposed to proceed via a transient nitrile enolate which is subsequently stereoselectively protonated by an intramolecular transfer of the proton from nitrogen to the nitronate α-carbon.